Who cares? : women's work, childcare, and welfare state redesign - Jenson, Jane (Studies in comparative political economy and public policy., 2001)
"By focusing on childcare and systematically comparing national experiences in Belgium, France, Italy, Sweden, and the European Union, Who Cares? provides detailed information on recent social policies and a clear perspective on welfare state redesign. Many countries have now designed childcare policies to reconcile family and work. Some encourage parents to provide their own childcare by granting parental leave; others encourage parents to stay at work by supporting childcare services. Using the case of childcare policy, the contributors to this volume examine how public policy choices over the last three decades have been fashioned by specific understandings of the gendered division of labour."--Jacket